Knowledge of caregivers on the risk factor knowledge factors of otitis media (2012)
Introduction: Otitis media (OM) is common in children. In developing countries, it is the most common cause of hearing impairment. Many factors predispose to OM, some of which are modifiable through lifestyle changes. This study aimed to determine the knowledge of caregivers on the risk factors (RFs) associated with OM and their willingness to modify their lifestyle to reduce the risk of OM. The impact of socioeconomic status (SES) on the knowledge and willingness in lifestyle alteration was also assessed. Materials and Methods: This is a prospective study using a modifi ed Ear Infection Survey questionnaire. The SES of caregivers/mothers was determined, and they were interviewed to determine their knowledge of RFs for OM and their willingness to undergo lifestyle modifi cations. Results: One hundred caregivers (96 females) were interviewed, majority of whom (81%) were in the higher SES. There were signifi cant differences between low and high SES in day care attendance, siblings and parents with history of OM. Apart from daycare attendance and household smokers, all other RFs were higher among the lower SES. Individuals from low SES background had poorer knowledge of the RFs for OM. A strong willingness to modify behavior to avert a surgical procedure for OM is seen in both groups. Conclusion: Caregivers in both SES groups were willing to undergo behavioral modifi cations in reducing the risk of OM; utilizing this knowledge in educational programs will help to reduce the prevalence of OM in children. This must be coupled with training and encouragement of health workers to disseminate information on RFs of OM